The EU and the crime of aggression after Kampala through the lens of effective multilateralism - Saraiva, Maria Francisca (2017)
The European Union and its Member States have a pivotal role to play at the International Criminal Court. The Kampala Conference (2010) adopted a definition of the crime of aggression and a regime establishing how the Court will exercise its jurisdiction over this crime. However, the EU did not have a Common Position in the run-up to the Kampala Conference and there were internal divisions betwen the members states of the EU and the EU itself at Kampala. Therefore, this paper discusses the role of the EU in defining the crime of aggression from the point of view of effective multilateralism adopted in 2003 as a core principle of its European Security Strategy